2013
DOI: 10.1038/clpt.2013.54
|View full text |Cite
|
Sign up to set email alerts
|

Model-Based Drug Development: A Rational Approach to Efficiently Accelerate Drug Development

Abstract: The pharmaceutical industry continues to face significant challenges. Very few compounds that enter development reach the marketplace, and the investment required for each success can surpass $1.8 billion. Despite attempts to improve efficiency and increase productivity, total investment continues to rise whereas the output of new medicines declines. With costs increasing exponentially through each development phase, it is failure in phase II and phase III that is most wasteful. In today's development paradigm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
208
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(210 citation statements)
references
References 59 publications
2
208
0
Order By: Relevance
“…As part of a model‐informed drug development strategy,23, 24 a model‐based meta‐analysis was carried out to evaluate the dose–response relationships for efficacy end points (major VTE and total VTE) and safety end points (major, clinically relevant, and total bleeding) of anticoagulants used for the prevention of VTE following THR and TKR surgery. A similar analysis was previously used to compare the various classes of anticoagulants and demonstrated that the therapeutic index relative to enoxaparin was greater for direct FXa inhibitors than for other classes of anticoagulants 21.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of a model‐informed drug development strategy,23, 24 a model‐based meta‐analysis was carried out to evaluate the dose–response relationships for efficacy end points (major VTE and total VTE) and safety end points (major, clinically relevant, and total bleeding) of anticoagulants used for the prevention of VTE following THR and TKR surgery. A similar analysis was previously used to compare the various classes of anticoagulants and demonstrated that the therapeutic index relative to enoxaparin was greater for direct FXa inhibitors than for other classes of anticoagulants 21.…”
Section: Discussionmentioning
confidence: 99%
“…As a key component of knowledge management,23, 24 these models can be used in conjunction with emerging data from investigational agents to help inform dose selection and study design, which will ensure efficient clinical development and adequate differentiation from current therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, most reports to date have summarized the return on investment of using QP approaches primarily in the domain of cost savings and efficiency gains 2, 3, 4. Here, we describe the potential of QP approaches to accelerate patient access to innovative therapies.…”
mentioning
confidence: 99%
“…There has been a near constant flow of new terms introduced into the literature1 in an attempt to capture this phenomenon: “MBDD,”2 “model‐facilitated” or “model‐informed drug development,”3 “Quantitative and Systems Pharmacology,”4 and “pharmacometrics.” Large pharmaceutical companies have begun to review, quantify, and report the successes derived from the adoption of a model‐based strategy, providing a thorough description of its implementation and impact 5, 6, 7. The US Food and Drug Administration (FDA) recently utilized mechanistic model‐based methodologies to design a postmarketing clinical trial8; serving as a clear demonstration of the increasing confidence in and adoption of model‐based techniques in pharmacology.…”
Section: Agent‐based Models: Introduction and Applicationsmentioning
confidence: 99%